Pendirian Perusahaan Equity Crowdfunding Bagi Pelaku Usahaberdasarkan Peraturan Otoritasjasa Keuangan Nomor 37/POJK.04/2018 - Hans Kristian Gozali (Jurnal Hukum Kaidah: Media Komunikasi dan Informasi Hukum dan Masyarakat, 2021)
Technological developments in the Industrial Revolution 4.0 era provide new solutions for business individuals in obtaining additional capital through financial technology (fintech). One of them is the crowdfunding system known as equity crowdfunding which is intended for individuals that want to develop their business but are constrained in terms of capital by utilizing the development of internet technology. In this regard, the government through the Financial Services Authority (OJK) has stipulated Financial Services Authority Regulation of the Republic of Indonesia Number 37/POJK.04/2018 concerning Crowdfunding Services through Information Technology-Based Share Offerings (Equity Crowdfunding).            That the formulation of the problems in this study is how legal certainty is in regulating the practice of equity crowdfunding in Indonesian laws and regulations, how is the legal protection for investors or investors who buy shares in the practice of equity crowdfunding and how is the role of OJK in the practice of equity crowdfunding. The research method used is normative juridical research, this research is descriptive analytical. Data collection techniques were carried out through library research methods. The data obtained were analyzed qualitatively and concluded deductively.Keywords: Legal Certainty, Legal Protection, Equity Crowdfunding and the Financial Services Authority